Meta-Analisis Kualitatif Kajian Ilmiah Self Regulated Learning dalam Pembelajaran Matematika: Qualitative Meta-Analysis of Scientific Studies of Self Regulated Learning in Mathematics Learning - Latifah, Kholifah Nur; Sukirwan; Anwar Hadi Firdos Santosa, Cecep (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2022)
Several studies on self-regulated learning show that self-regulated learning is related to learning outcomes. In this study it was concluded that individuals will get good results, if they have good self-regulation. But the researchers found research that contradicted this conclusion. The purpose of this study was to find out how to make self-regulated learning directly proportional to student learning outcomes. Research that can be done to find out the description of the research results is a meta-analysis. Subjects were taken from two scientific databases, namely the thesis database for students majoring in Mathematics Education UNTIRTA and scientific articles from the International Journal of Science and Mathematics Education about self-regulated learning. The data analysis technique used in this study is identification, screening, eligibility, and inclusion. The conclusion of this study can be concluded that in determining the way in which self-regulated learning is directly proportional to student learning outcomes, it can be seen from various research categories. Keyword: Self Regulated Learning; Meta-Analysis